PERBEDAAN KEKERASAN PERMUKAAN ENAMEL GIGI DESIDUI TERHADAP POLA KONSUMSI IKAN LAUT Studi Pada Anak Usia 5 – 7 Tahun di Desa Teluk Awur dan Desa Jlegong Kabupaten Jepara - Astrid Nurlaila Noviasari; Sandy Christiono; Eko Hadianto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: The descrease of the tooth surface hardness can be aﬀected by the microorganisms activity that ultimately cause the damage of the tooth surface hardness. The process of remineralization is needed to restore the lost minerals. A fsh that contain of calcium, phosphorus and ﬂuoride can help the process of remineralization. The purpose of this research is to determine the diﬀerence of fsh consumption pattern toward the enamel hardness of deciduous teeth at Teluk Awur Village and Jlegong Village of Jepara Regency.Methods: This research methode was experimental type laboratoris with research design of post only control group and consist of two groups that were coastal area and non coastal area group. The sample used was the lower anterior decicuous teeth that revocation of 14 units. The tooth hardness was measured with the Micro Vickers Hardness Tester, followed by data analysis with Independent T-test.Result: The results showed that the mean of surface hardness of deciduousteeth in Teluk Awur Village was 1009.91 VHN while in Jlegong Village was 691.31 VHN. The Independent T-test showed the signifcance result was 0.012 (P <0,05) and interpret that there were diﬀerentiation in fsh consumption patterns between the groups toward the enamel hardness of deciduous teeth.Conclusion: The conclusion of this research showed that there is diﬀerentiation of enamel hardness of deciduous teeth at the age of 5 - 7 years at Teluk Awur Village and Jlegong Village which have got treatment to consume fsh.